TELAAH PEMIKIRAN EKONOMI ISLAM : YAHYA BIN ADAM AL-QARASHI (±140 H/755 M – 203 H/818 M) - Juliana Juliana; Firmansyah Firmansyah; Bangkit Pratama (Jurusan Akuntansi Politeknik Negeri Bandung, 2016)
Abstract: Most people know the works of al-Kharaj made by Abu Yusuf. Yahya bin Adam, who has a full name Yahya bin Adam bin Sulaiman al-Qarashi al-‘Umawi al-‘Umawi al-Ahwal al-Kufi, with Abu Zakariya's real name is one of the ulama or muslim scholar who also wrote kitab al-Kharaj lived during the Abbasid Caliphate in the reign of Abu Ja’far al-Manshur to al-Ma’mun. Yahya bin Adam is of people who contribute to the complete theories of taxation in Islam other than Abu Yusuf. In this research using literature study, a method that is taken by using various references are books or journals related in which includes Yahya bin Adam perspectives relating to economy. From various references can conclude some thoughts Yahya bin Adam typical associated with Economic contained in the book of al Kharaj, namely the concept of Kharaj and Jizya, 'Usyur, the ban on buying land Kharaj, the concept of taxation, price concept, and how to revive the dead land (Ihya’al-Mawaat). Keywords: Yahya bin Adam, Kharaj, Jizya, Ihya’al-Mawaat